2015
DOI: 10.1002/ajhb.22715
|View full text |Cite
|
Sign up to set email alerts
|

Gross motor coordination and weight status of Portuguese children aged 6–14 years

Abstract: These centile curves can be used as reference data in Portuguese children and youth, aged 6-14 years. Being overweight or obese was a major limitation in MC tests and, therefore, of the children's health- and performance-related physical fitness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
29
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 34 publications
7
29
0
3
Order By: Relevance
“…Whilst children generally improve their GMC with age, in the current study, a nonlinear trend in GMC across time was found suggesting a performance peak at 9 years of age, that is, the exponent of age square remains negative in all models. Yet, available reports on GMC centile charts in Portuguese children do not clearly show a plateau around 9 years of age. Our finding is perhaps due to the fact that our serial data stop at 9 years.…”
Section: Discussionmentioning
confidence: 92%
“…Whilst children generally improve their GMC with age, in the current study, a nonlinear trend in GMC across time was found suggesting a performance peak at 9 years of age, that is, the exponent of age square remains negative in all models. Yet, available reports on GMC centile charts in Portuguese children do not clearly show a plateau around 9 years of age. Our finding is perhaps due to the fact that our serial data stop at 9 years.…”
Section: Discussionmentioning
confidence: 92%
“…The present study suggests that GMC levels may be negatively associated with BMI, controlling for age, sex and altitude sites. Some reports to date have shown negative associations between BMI and GMC (Antunes et al, 2015;D'Hondt et al, 2011;Graf et al, 2004;Lopes, Stodden, Bianchi, Maia, & Rodrigues, 2012;Martins et al, 2010). A recent longitudinal study showed that GMC developmental levels were strongly related to children's weight status, attributed to BMI, per se, a negative role in predicting motor competence (D'Hondt et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of self-report instruments to obtain this information is common [ 32 , 74 , 75 ]. Additionally, the Baecke questionnaire is regularly used in Portuguese studies with highly reliable results [ 22 , 76 78 ]. This study also has several strengths, including: (1) the use of a broad approach of health-related physical fitness with siblings, (2) the large sample size of siblings (3) the examination of important time windows in children’s growth and development, (4) the use of standard measurement protocols and highly reliable data, and (5) the use of a novel, multilevel statistical methodology.…”
Section: Discussionmentioning
confidence: 99%